Hubungan Tingkat Pendidikan dan Status Pekerjaan ibu dengan Keberhasilan Imunisasi Dasar pada usia 0-11 Bulan di Desa Buddagan Pademawu Pamekasan - Lianita Primi Octaviana; Dina Novarita KW (NHM PRESS, 2022)
Immunization is one of the government's programs in reducing the number of infections in infants. There are several types of basic immunizations given to infants from 0-11 months of age, including HB0, BCG, DPT, Polio, Hib and Campak. This type of administration in immunization adjusts to the age of the baby. One of the problems if the baby is not immunized will transmit the number of diseases one of the smallpox outbreaks. The number of immunization achievements in 2021 is still below the target of 93.6%. The purpose of this study was to determine whether there is a relationship between education and employment levels on the success of basic immunization in Buddagan Village, Pademawu District, Pamekasan Regency This research method uses an analytical survey with a Cross Sectional approach and the sampling technique of this study uses a total simple random sampling there are 45 mothers who have babies aged 0-11 months sample. Data analysis in this study used Regression test Data analysis in this study used Regression test The results showed that there was no influence on the level of education on the success of basic immunization aged 0-1 months in Buddagan village, Pademawu District, Pamekasan Regency with a p value of 0.437. As for the job variable, there is a significant influence with a P value = 0.025 with the success of basic immunization aged 0-1 months in Buddagan village, Pademawu District, Pamekasan Regency